Epstein-Barr Virus Encephalitis in an Immunocompetent Child: A Case Report and Management of Epstein-Barr Virus Encephalitis - KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT (HINDAWI LTD, 2016)
Epstein-Barr virus (EBV) usually causes mild, asymptomatic, and self-limited infections in children and adults; however, it may occasionally lead to severe conditions such as neurological diseases, malignant diseases, hepatic failure, and myocarditis. Epstein-Barr virus-related neurological disorders include meningitis, encephalitis, and cranial or peripheral neuritis, which are mostly seen in immunocompromised patients. The therapeutic modalities for EBV-related severe organ damage including central nervous system manifestations are still uncertain. Herein, we describe a seven-year-old boy with EBV encephalitis who presented with prolonged fever, exudative pharyngitis, reduced consciousness, and neck stiffness. Cranial magnetic resonance imaging showed contrast enhancement in the bilateral insular cortex and the right hypothalamus. The diagnosis was made by EBV-DNA amplification in both the blood and cerebrospinal fluid samples. He was discharged with acyclovir therapy without any sequelae.
Keywords: INFECTIONS; ENCEPHALOMYELITIS